The Develpment of Microwave Absorber From Oil Palm Shell Carbon - Yusof, Ahmad Anas (2004)
A method for reducing palm shell residues has been investigated. Using pyrolysis technique, the residues are transformed into carbons, which are later used as a lossy elements in microwave absorber application. The microwave properties of permittivity,( Îµ), loss tangent, (tan Î´) and absorption performance of microwave absorber utilizing palm shell carbon mixed with unsaturated polyester resin were studied in the microwave region of 8 to 12 GHz (X-band). The measurement of ( Îµ) and (tan Î´) emphasize on the influence of carbon concentration (mass %) and pyrolysis temperature in the production of the carbon. It was found out that by increasing carbon pyrolysis temperature, an increase in ( Îµ) and (tan Î´) had been observed. The increase of carbon concentration inside each measured sample also influenced the increase of ( Îµ) and (tan Î´) condition. The optimum (tan Î´) was found by using 30% carbon pyrolysed at 800oC temperature, suggesting significant contribution in dielectric loss properties of the material. The preparation of microwave absorber by utilizing 30% mass concentration of palm shell carbon mixed with unsaturated polyester resin had been tested for microwave absorption. The amplitude of the absorption was relatively measured to a metal plate reference, which resulted in a various microwave absorption with respect to the thickness of the absorber. Moderate microwave absorption around - 10 dB was achieved for most samples within the same frequency band, with maximum absorption of - 30 dB for a thickness up to 75 mm. All the data indicates the possibility of using pyrolysed carbon derived from palm shell residues in providing an affordable solution for microwave technology as well as an alternative in managing the increase of the residues throughout the country.